2021
DOI: 10.1167/jov.21.3.14
|View full text |Cite
|
Sign up to set email alerts
|

Geometrically restricted image descriptors: A method to capture the appearance of shape

Abstract: Shape perception varies depending on many factors. For example, presenting a stimulus in the periphery often yields a different appearance compared with its foveal presentation. However, how exactly shape appearance is altered under different conditions remains elusive. One reason for this is that studies typically measure identification performance, leaving details about target appearance unknown. The lack of appearance-based methods and general challenges to quantify appearance complicate the investigation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 97 publications
(112 reference statements)
1
1
0
Order By: Relevance
“…For example, using a gaze-contingent peripheral presentation and appearance capture (drawing) paradigm, frequent omissions and truncations of elements in letter and letter-like targets indicated target diminishment in crowding ( Sayim & Wagemans, 2017 ). Similar results, possibly due to “self-crowding” ( Martelli, Majaj, & Pelli, 2005 ; Zhang, Zhang, Liu, & Yu, 2009 ), were found with complex, peripherally presented letters and letter-like shapes in isolation ( Melnik, Coates, & Sayim, 2021 ). The investigation of errors in peripherally presented lower-case letter trigrams revealed a similar pattern of diminishment in crowding, as letter features appearing in both a flanking letter and the target letter (such as an ascender or descender) were often omitted in the reported target ( Coates et al, 2019 ).…”
Section: Introductionsupporting
confidence: 72%
“…For example, using a gaze-contingent peripheral presentation and appearance capture (drawing) paradigm, frequent omissions and truncations of elements in letter and letter-like targets indicated target diminishment in crowding ( Sayim & Wagemans, 2017 ). Similar results, possibly due to “self-crowding” ( Martelli, Majaj, & Pelli, 2005 ; Zhang, Zhang, Liu, & Yu, 2009 ), were found with complex, peripherally presented letters and letter-like shapes in isolation ( Melnik, Coates, & Sayim, 2021 ). The investigation of errors in peripherally presented lower-case letter trigrams revealed a similar pattern of diminishment in crowding, as letter features appearing in both a flanking letter and the target letter (such as an ascender or descender) were often omitted in the reported target ( Coates et al, 2019 ).…”
Section: Introductionsupporting
confidence: 72%
“…Importantly, while crowding is usually assumed to affect target identification but not detection (Livne & Sagi, 2007;Pelli et al, 2004), recent studies showed that target parts were unnoticed under crowding (Coates et al, 2017;. Such "omission errors" ; see also Melnik et al, 2021) were suggested to be due to "redundancy masking," a recently discovered phenomenon where the number of perceived items in repeating patterns is reduced (Sayim & Taylor, 2019;Yildirim et al, 2020Yildirim et al, , 2021b. Redundancy masking has been shown to occur when as few as 3 items were presented (Sayim & Taylor, 2019;Yildirim et al, 2020Yildirim et al, , 2021b.…”
Section: Introductionmentioning
confidence: 99%